Internationalisation in practice in Australian independent secondary schools: a global-local nexus?. Issue 2 (4th March 2017) - Fielding, Mark; Vidovich, Lesley
ABSTRACT: The phenomenon of internationalisation of education in the twenty-first century has developed more rapidly and has been the subject of more research in higher education than in the schooling sector. This paper conducts a comparative analysis of the perspectives of school leaders, teachers and students about 'internationalisation in practice' in two case-study Australian independent secondary schools that adopted different approaches to internationalisation. Theoretical lenses of both interpretivism and critical theory were used to guide the research at different stages. Both qualitative and quantitative methods were used. Findings indicate that whilst globalisation is having a powerful impact on schools, local contextual factors such as school ethos, school resources, teacher values and parent demographics and expectations play a significant part in shaping how schools engage with internationalisation. Wider implications for equity, teacher education and further research and theory development are also discussed.